Analisis Kinerja Keuangan berdasarkan Rasio Keuangan pada PT. BPR. Saptacristy Utama - PRADNYANI, NI LUH KOMANG AYU; USTRIYANA, I NYOMAN GEDE; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol 6 No 1 (2017), 2017)
Analysis of Finece Performance Base on Fund Finance Ratio of PT. BPR. Saptacristy Utama Rural Banks (BPR) is a formal financial institution that has a function as a financialintermediary, especially on the national microfinance system. The study aimed tofind out the financial performance of PT. BPR. Saptacristy Utama when it wasanalyzed based on the financial ratios during the period of 2011 to 2015. Based onthe results of the financial analysis, liquidity ratio is categorized good, when viewedfrom the average cash ratio and the average loans to deposit ratio. The solvency ratiois said to be good, judging by the average capital adequacy ratio. Activity ratio isquite good when viewed from the multiplier leverage ratio and asset utilization ratiothat continue to increase. The profitability ratio is classified to be good,as can beseen on the average net profit margin, return on assets and return on equity. PT. BPR.Saptacristy Utama is expected to maintain its financial performance by strengtheningits business activities to increase the amount of its assets, the amount of thedistribution of funds in the form of loans and the placement of funds in other banksshould also be increased, revenue of operations and profits for subsequent yearsshould beincreased, as well as improving sale and service to its customers andprospective customers.
Keywords: rural banks; finance performance; financial ratioanalysis